2015
DOI: 10.1038/ncomms8429
|View full text |Cite|
|
Sign up to set email alerts
|

Photogated humidity-driven motility

Abstract: Hygroinduced motion is a fundamental process of energy conversion that is essential for applications that require contactless actuation in response to the day–night rhythm of atmospheric humidity. Here we demonstrate that mechanical bistability caused by rapid and anisotropic adsorption and desorption of water vapour by a flexible dynamic element that harnesses the chemical potential across very small humidity gradients for perpetual motion can be effectively modulated with light. A mechanically robust materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
158
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(161 citation statements)
references
References 31 publications
3
158
0
Order By: Relevance
“…The shape transformations of biological organisms [1][2][3][4][5][6] have been the inspiration for many products in the field of artificial muscles, [7][8][9][10][11][12][13] soft robotics, [14][15][16][17][18][19] sensors 20 and complex shape engineering. 21,22 For example, the leaves of the Venus flytrap snap together to capture insects by virtue of the synergy between the hydroelastic instability and asymmetric expansion of the inner and outer surfaces at the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…The shape transformations of biological organisms [1][2][3][4][5][6] have been the inspiration for many products in the field of artificial muscles, [7][8][9][10][11][12][13] soft robotics, [14][15][16][17][18][19] sensors 20 and complex shape engineering. 21,22 For example, the leaves of the Venus flytrap snap together to capture insects by virtue of the synergy between the hydroelastic instability and asymmetric expansion of the inner and outer surfaces at the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the currently known light-driven LCEs have been constructed by introducing azobenzenes into polymer networks. [1][2][3]5,[11][12][13][14][15][16][17][18][19][21][22][23][24][25] The trans-to-cis isomerization under UV light and cis-to-trans isomerization with visible light makes the azobenzene group a robust, durable, and fatigueless photoswitchable unit that is now ubiquitous in photoactive materials. [26][27][28] trans-Azobenzene is a liquid crystal mesogen, which stabilizes liquid crystal phases, while the cis-azobenzene is not a liquid crystal mesogen and usually destabilizes the liquid crystal phases.…”
Section: -25mentioning
confidence: 99%
“…Previous work has shown that the shape of AG-based actuators is the primary factor that determines their bending performance. 20,22 To investigate these effects, the response to sunlight of F-Azo@AG lms with different shapes were studied. F-Azo@AG lms were cut into strips with a xed length and different widths (length, 7 mm; width, 1, 3, or 5 mm) and clamped using a support (Fig.…”
Section: -50mentioning
confidence: 99%
See 2 more Smart Citations